The Effectiveness of Law Enforcement against Non-Compliant UN Taxpayers - Chairany amsi; Zahra Amalia; Varadila; Ariston; Yusuf Matunry; Dinda Nur Salsabilah (ISNU Sumatera Utara, 2025)
Place law enforcement against taxpayers who do not comply in paying the Land and Building Tax (PBB) is an important issue in the regional tax system. This study aims to analyze the effectiveness of law enforcement efforts against violations of UN obligations and the obstacles faced by local governments in their implementation. The method used is an empirical juridical approach with a field study at the regional revenue office in one of the districts/cities. The results of the study show that law enforcement against non-compliant taxpayers has not run optimally due to weak socialization, low sanctions given, and lack of integration of land and building ownership data. Regulatory reform and synergy between law enforcement officials, local governments, and financial institutions are needed to improve tax compliance.